2020
DOI: 10.1027/0227-5910/a000638
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Peer-Led Implementation of a Suicide Prevention Gatekeeper Training Program for College Students

Abstract: Abstract. Background: Research on models of implementation that enable widespread dissemination of suicide prevention to young adults is needed to address the critical public health issue of suicide among young adults. A peer-to-peer implementation approach may increase widespread dissemination of suicide prevention on college campuses.  Aims: The current study involved the evaluation of a peer-led implementation of the evidence-based program Question, Persuade, and Refer Gatekeeper Training for Suicide Preven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“… 3 To address the serious mental health issue of suicide among youth, an approach that enables the dissemination and understanding of suicide prevention to youths is needed. 4 …”
Section: Introductionmentioning
confidence: 99%
“… 3 To address the serious mental health issue of suicide among youth, an approach that enables the dissemination and understanding of suicide prevention to youths is needed. 4 …”
Section: Introductionmentioning
confidence: 99%
“…While the specific predictors vary, our prediction rate is consistent with the 84-91% accuracy reported in the Belgian university student population (Mortier et al, 2017) which is the study most comparable to this current study in terms of predicting 1year incidence. In addition, one study of French college students that predicted any future STB rather than incidence (new cases) during a 1-year prediction period, reported 80% accuracy (with prior STB being among the strongest predictors of future STB) (Macalli et al, 2021), and another study of Scottish young adults (not exclusive to university students that also predicted any future STB rather than first incidence during a 1-year prediction period, reported 81-83% accuracy (van Mens et al, 2020) posed for college students, though the evidence so far for their effectiveness in preventing STB is limited (Samuolis et al, 2020;Wolitzky-Taylor et al, 2020). Sleep duration is another modifiable factor that other studies in college students have also found to be associated with STB (Becker et al, 2018;Khader et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Interventions can foster improving social skills and social support networks. Peer gatekeeper interventions have been proposed for college students, though the evidence so far for their effectiveness in preventing STB is limited (Samuolis et al, 2020; Wolitzky‐Taylor et al, 2020). Sleep duration is another modifiable factor that other studies in college students have also found to be associated with STB (Becker et al, 2018; Khader et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, Katsumata et al’s (2017) study of a gatekeeper program for Japanese university students also had positive results. Studies in universities in the US have shown that gatekeeper interventions have improved students’ ability to identify suicidal peers and increase their willingness to intervene (Samuolis et al, 2020), as well as increase the number of referrals to mental health specialists, especially among females (Rallis et al, 2018). However, some studies in Australia, US, and Netherlands have demonstrated no increase in help-seeking (Chan et al, 2014; Harrod et al, 2014; Lipson et al, 2020; Rallis et al, 2018; Terpstra et al, 2018).…”
Section: Discussionmentioning
confidence: 99%